Ranaviruses: Emerging Pathogens of Ectothermic Vertebrates - Gray, Matthew J; Chinchar, V. Gregory (Springer Nature, 2025)
This is a open access book. Ranaviruses, double-stranded DNA viruses (family Iridoviridae) that cause systemic, life-threatening disease in a variety of amphibians, reptiles and fish, have contributed to mass die-offs of both wild and captive populations around the globe. These viruses are emerging and increasingly responsible for population declines of ectothermic vertebrates. Because amphibians, reptiles, and freshwater turtles are suitable hosts and among the most imperiled vertebrate taxa in the world, ranaviruses can have significant impacts on biodiversity and ecosystem function. Additionally, many fish that are raised in aquaculture facilities and traded internationally are suitable hosts; thus, the potential economic impact of ranaviruses is significant. Ranaviruses also serve as a model for understanding viral replication and gene function among large double-stranded DNA viruses, e.g., poxviruses, asfarvirus, and ascoviruses. Lastly, study of the host immune response to ranaviral disease and the identification of viral immune evasion genes that negatively regulate host immune functions provide insight into which specific immune elements are most important in protecting host species against severe disease. The effort to produce a 2nd edition of our earlier work grew out of a recent meeting (1st Global Amphibian and Reptile Disease Conference) held in August 2022. Given the continued research in ranaviruses and ranaviral disease since the first edition, this new book updates the latest information on ranaviruses and provides guidance on how to monitor and manage ranaviruses in cold-blooded vertebrate populations.